Epidemiology and factors associated with preterm births in multiple pregnancy: a retrospective cohort study - Samita Seetho; Kiattisak Kongwattanakul; Piyamas Saksiriwuttho; Kaewjai Thepsuthammarat (BMC, 2023)
Abstract Objective Multiple pregnancies carry an increased risk of maternal and perinatal complications, notably prematurity. Few studies have evaluated the risk factors for preterm births in multiple pregnancies within the Thai population. This study aims to ascertain maternal and perinatal outcomes and identify factors linked to preterm births in multiple pregnancies. Methods This study was carried out at Khon Kaen University, Faculty of Medicine, Department of Obstetrics and Gynecology in Thailand. We reviewed the medical records of women with multiple pregnancies who delivered at a gestational age of more than 20 weeks between January 1, 2012 and December 31, 2021. We excluded patients with incomplete data or those for whom data were missing. Results Out of 21,400 pregnancies, 427 were multiple pregnancies, constituting approximately 1.99%. Over the ten-year period, 269 multiple pregnancies (65.1%) resulted in preterm births. Of these, 173 (64.3%) were monochorionic twins, and 96 (35.7%) were dichorionic twins. Monochorionic twins had a notably higher rate of preterm delivery (AOR, 2.06; 95%CI 1.29-3.30). Vaginal delivery was observed in 7.9% of the cases, while cesarean sections were performed for both twins in 91.5% of cases. In 0.5% of the cases, only the second twin was delivered by cesarean section. In terms of neonatal outcomes, 160 infants (19.4%) weighed less than 1,500 g at birth, and there were 78 perinatal deaths (9.4%). Birth asphyxia was noted in 97 cases (20.2%) among monochorionic twins and in 28 cases (8.1%) for dichorionic twins. Conclusion The prevalence of multiple pregnancies was 1.99%, with 65.1% resulting in preterm births. Neonatal complications were notably more frequent in monochorionic twins. Monochorionic placenta and antepartum complications emerged as significant risk factors for preterm birth.